The College of Environmental Science and Engineering of Tongji (College of Environmental Science and Engineering, Tongji University, 2002)
United Nations Environment Programme (UNEP) and Tongji University signed an agreement on May 9th 2002 to jointly set up UNEP-Tongji Institute for Environment and Sustainable Development for the purpose of strengthening scientific research and providing educational programs in environment and sustainable development. The Institute will introduce and strengthen the international environmental education and scientific research and design its educational programs for undergraduate and postgraduate students with support from the College of Environmental Science and Engineering and other related colleges of Tongji University. In the Institute, importance is attached to the teaching of planning, management and development against the background of environmental science and technology. Specialties in water resource reservation, industrial ecology and environment management, eco-city planning and management, energy and environment, economic development and ecological protection, environmental informatics, environmental monitoring and remote control, environmental value analysis, regional and global environmental studies will be developed for the cultivation of senior technical and managerial personnel of sustainable development.